2005
DOI: 10.1177/1534735405282842
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: The Pharmacological Antioxidant Amifostine—Implications of Recent Research for Integrative Cancer Care

Abstract: Amifostine is a pharmacological antioxidant used as a cytoprotectant in cancer chemotherapy and radiotherapy. It is thought to protect normal tissues relative to tumor tissue against oxidative damage inflicted by cancer therapies by becoming concentrated at higher levels in normal tissues. The degree to which amifostine nevertheless accumulates in tumors and protects them against cancer therapies has been debated. Guidelines have been published that direct its use in chemotherapy and radiation, taking into con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…An in vitro study demonstrated that amifostine inhibits DNA platination and is also able to reverse part of the cisplatin-DNA adducts formed, but different from the other thiols tested (DDTC and STS), and amifostine does not interfere in the antitumor efficacy of cisplatin. Additionally, clinical studies with amifostine have not provide the evidence of impairment of antitumor activity (Block and Gyllenhaal 2005). The relative success of amifostine has been attributed to the selective formation, uptake, and accumulation of the active metabolite WR1065 in normal tissues (Treskes et al 1992;Block and Gyllenhaal 2005).…”
Section: Intrinsic or Mitochondrial Apoptotic Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…An in vitro study demonstrated that amifostine inhibits DNA platination and is also able to reverse part of the cisplatin-DNA adducts formed, but different from the other thiols tested (DDTC and STS), and amifostine does not interfere in the antitumor efficacy of cisplatin. Additionally, clinical studies with amifostine have not provide the evidence of impairment of antitumor activity (Block and Gyllenhaal 2005). The relative success of amifostine has been attributed to the selective formation, uptake, and accumulation of the active metabolite WR1065 in normal tissues (Treskes et al 1992;Block and Gyllenhaal 2005).…”
Section: Intrinsic or Mitochondrial Apoptotic Pathwaymentioning
confidence: 99%
“…Additionally, clinical studies with amifostine have not provide the evidence of impairment of antitumor activity (Block and Gyllenhaal 2005). The relative success of amifostine has been attributed to the selective formation, uptake, and accumulation of the active metabolite WR1065 in normal tissues (Treskes et al 1992;Block and Gyllenhaal 2005).…”
Section: Intrinsic or Mitochondrial Apoptotic Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…It was well documented that CDDP could be selectively accumulated in the kidney to a higher level, in which the abundant and abnormal production of ROS directly involves in the oxidative damage of cellular macromolecules, and then induces the proximal tubule necrosis and/or apoptosis [1,3] . Indeed, several antioxidant agents have been reported to ameliorate the nephrotoxicity of CDDP, such as cilastatin [7] , sildenafil [8] and amifostine (WR 2721), which was approved by FDA to reduce the cumulative nephrotoxicity induced by CDDP via scavenging the free radicals [9] . Novel antioxidants, therefore, might be potential chemoprotectants for preventing the kidney injury induced by CDDP [9,10] .…”
Section: Introductionmentioning
confidence: 99%